Análise exploratória de variáveis associadas à hipermobilidade articular comuns a síndrome de Ehlers-Danlos hipermóvel - Lamari, Mateus Marino (2017)
Ehlers-Danlos Syndrome Hypermobility or Ehlers-Danlos Hypermobile Syndrome (EDS-HT/hEDS) is the only type of EDS with no confirmed cause, predisposing to musculoskeletal and extraskeletal affections. It is multisystemic with clinical variability affecting skin, ligaments, joints, blood vessels and internal organs. It accounts for 80-90% of the cases of EDSs, being the systemic hereditary disorder of connective tissue more common in humans. Most of its clinical manifestations are associated with joint hypermobility (JH), which is generally neglected and considered as a harmless ability by most health professionals due to their lack of knowledge. Objectives: In a sample of children and adolescents, to determine the frequency of JH in a sample of children and adolescents, to characterize the sample according to body abilities, clinical signs and symptoms such as orthopedic, dermatological, neurological, psychosocial, gastrointestinal, bucomaxillofacial and otorhinolaryngological, and to identify variables associated with JH common to EDS-HT/hEDS syndrome. Casuistic and Methods: This is a cross-sectional study with a sample of 57 children and adolescents, between five and 16 years of age, both sexes, undergoing to multiprofessional care at the JH and EDS outpatient clinic of Hospital de Base of São José do Rio Preto and in the Gato de Botas Unit-Project in partnership with the Medical School of São José do Rio Preto -FAMERP. Data collection was performed from May 2016 to February 2017, by application of a questionnaire and analyzes by Beighton scores to characterize JH and its associations, as well as the Brighton criteria to verify the variables common to these criteria. Data were tabulated and interpreted by descriptive statistical analysis from the calculations of measures of central tendency, dispersion and frequency counts in the Statistical Package for Social Science (SPSS) Program, Software version 24. Results: Beighton's analysis showed a score ≥4 for JH in the majority of the sample (89.5%), mainly in the upper limbs. The ability to sit in "W" position and to use atypical pen support for writing were the body skills with higher frequency. Among the most prevalent clinical manifestations were musculoskeletal pain (70.2%), skin alterations (84.2%), structural changes in the feet (54.0%) and in the face (84.2%), sleep disorder (42.1%), fatigue (28.1%), gastrointestinal dysfunction (38.6%), psychosocial (36.8%) and neurological (40.3%) manifestations. Approximately half of the sample of the evaluated individuals (43.7%) fulfilled Brighton's main criteria for the diagnosis of EDS-HT/hEDS. Conclusion: JH and musculoskeletal and extraskeletal systemic manifestations are frequent characteristics in children and adolescents, and approximately half meet the criteria for EDS-HT/hEDS. Thus, characterizing children and adolescents with JH and early identification of signs and symptoms common to EDS-HT/hEDS and other manifestations is extremely important for early intervention.